E-MODULE BASIC AERONAUTICAL FIXED SERVICE BASED ON LEARNING MANAGEMENT SYSTEM - Nizar Alwi, Nobrian; Maharani Sukma, Meita; Hadi Rantelinggi, Parma; Syahrul Aman; Rochmawati, Laila (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Aeronautical Fixed Service is one of the courses in the Diploma 3 Aeronautical Communication Study Program which studies telecommunications services between point to point aimed at air navigation safety and the creation of regular, efficient and economical air service operations. For purpose supports the learning activities of flight safety cadets and users who want to add insight into the world of aviation. This research uses a type of development research or Research and Development (R & D). The model developed in this study uses the Waterfall model, which aims to design and develop an LMS filled with Aeronautical Fixed Service (AFS) course material. The result of this research is an Emodule that contains learning material for the Basic Aeronautical Fixed Service course in accordance with the academic syllabus of the Aviation Communication study program. And then In the results of the average calculation, a percentage index of 87.71% was obtained in the strongly agree category and the remaining 12.29% were not researched more